239 VASOSPASTIC ANGINA: A CASE OF COMPLETE FUNCTIONAL ASSESSMENT. (15th December 2022) - Pricoco, Francesco; Scala, Antonella; Pompei, Graziella; Campo, Gianluca; Tebaldi, Matteo; Biscaglia, Simone
Abstract: Introduction: Vasospastic angina is defined as a focal or diffuse spasm of the arterial wall of an epicardial coronary artery due to muscle cells hyperreactivity caused by an increased calcium sensitivity. Clinical presentation typically consists in chronic story of rest and/or effort typical chest pain, episodes of ST elevated or not ST elevated myocardial infarction, arrhythmias or cardiac arrest; an increased vagal tone, drugs, allergic reactions or the exposure to extreme cold also can trigger vasospasm. Clinical case: 73 years old dyslipidemic woman; in past medical history thyroidectomy and radiotherapy for carcinoma and right quadrantectomy with radiotherapy and hormonal therapy for breast cancer. In 2017 admission to cath-lab for non-ST elevation myocardial infarction (NSTEMI) with the evidence of mild left coronary artery disease without critical obstructive stenosis (MINOCA). For the persisting of effort angina and dyspnea (NYHA and CCS II-III), started Diltiazem therapy (60 mg x3) with clinical benefit. In 2020, due to the onset of new episodes of angina, started Ranolazine therapy. In June 2022, for the worsening of clinical symptoms, was evaluated with a Coronary CT, that showed a 65% stenosis at right coronary-acute marginal bifurcation and mild disease on left coronary artery, and then was admitted for an elective coronary angiography, with no evidence of epicardial artery critical stenosis. At the functional evaluation FFR, CFR and IMR (>0.80, 2.5 and 18) demonstrated normal coronary flow reserve and good microcirculation function. For the suspicion of vasospastic angina, acetylcholine test was performed with the evidence of mid-distal left anterior descending artery total occlusion, angina onset and ECG changes, promptly regressed with nitrates administration (Figure 1 ). Patient was discharged with the optimization of medical therapy with Diltiazem 120 mg x3, with clinical benefit. Figure 1 Left anterior descending artery pre and post acetylcholine administration Conclusions: To date vasospastic angina remains underdiagnosed. Functional evaluation of coronary arteries plays a fundamental role in the diagnostic algorithm of the disease and should always be investigated in case of patients with typical symptoms and the absence of critical epicardial stenosis. Further investigations are required to better explain pathogenesis and to identify affected patients in shorter times to ensure early optimized medical therapy.